All Stories Are Not Alike: A Purpose-, Content-, and Valence-Based Taxonomy of Patient Narratives in Decision Aids. (January 2013) - Shaffer, Victoria A.; Zikmund-Fisher, Brian J.
The use of patient stories in decision aids is a highly controversial practice. However, the resulting debates and research have yielded little consensus about the impact of patient stories due to vague operational definitions of narratives. In this article, we argue that narratives are not homogeneous in either content or effect and hence should not be considered a single construct in research. The purpose of this article is to provide a taxonomy that guides both the development of decision aids and future research on this topic. We define three dimensions of narratives that are likely to moderate their impact on decision making: 1) the purpose of the narrative, 2) the content of the message, and 3) the evaluative valence, or overall tone, of the message. In addition, we describe predicted effects of different types of narratives on decision making and discuss their potential interactions. Our taxonomy provides a framework that will allow for the precise documentation of different narrative types, the use of appropriate outcome measures, and a systematic evaluation of narratives in all types of decision aids. Failures to recognize the complex structure of narratives will result both in research that does little to inform our understanding of the impact of patient stories and in the use of narratives in patient education materials that have unintended consequences on both decision processes and behavior.